(untitled) (One Health & Risk Management, 2024)
Introduction. Quality of life is a cornerstone in the assessment of modern medicine, surgery, and healthcare practices. This aspect is becoming increasingly important in healthcare due to the rapidly increasing power, variety, and cost of modern drugs and surgical techniques. The aim of this study was to assess and compare the quality of postoperative recovery in patients undergoing surgery for perforated ulcer. Material and methods. This observational, prospective study was conducted on 231 patients undergoing emergency surgery. Postoperative recovery was assessed using the GSRS and MOS SF-36. The control group for the studied parameters consisted of average data obtained from 42 healthy individuals from the general population, with similar socioeconomic status and age to the main group of the study. Results. The research presents an analysis of 231 patients, mostly men, which is considered statistically conclusive (p<0.0001), with a diagnosis of perforated gastroduodenal ulcer resolved by various surgical interventions. The majority of the patients were of working age, highlighting the significant social and economic impact of these issues. The remote follow-up period extended up to 10 years (average 7 years) after the primary surgery. The correlation between the life quality index and the surgical approach applied was statistically significant (p<0.001). In the comparative analysis, it was noted that, among all the surgical intervention methods, the groups undergoing ulcer excision, ulcer excision with vagotomy, and gastric resection yielded the least favorable results (p<0.001). The data obtained confirm that the GSRS and MOS SF-36 indices of life quality in patients undergoing the laparoscopic approach are statistically significantly better and more sustainable, impacting the effectiveness of treatment resolution (p<0.001). Conclusions. Life quality measures are increasingly used worldwide to assess surgical outcomes, as they focus on specific health conditions and are essential for detecting changes resulting from treatment, thereby assessing its effectiveness. The present study found that the differential selection of treatment tactics using modern minimally invasive technologies, especially laparoscopic suturing of perforated gastroduodenal ulcer, demonstrated significantly better efficiency compared to traditional, especially radical, operations.